Analysis of Completeness of Medical Records in Inpatient Patients at Dr. Pirngadi Hospital, Medan City - Harahap, Reni Agustina; Wulan, Retna; Lubis, Eli Marlina; Nurzannah, Mifta; Oktaviani, Ririn; Tampubolon, Julianti (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2024)
Recording of medical record files must meet the minimum standards of hospital services. The purpose of this study was to analyze the completeness of medical record documents for inpatients at RSUD DR. Pirngadi, Medan City. This study used a quantitative method with a descriptive approach, the data analysis used was a univariate test. Of the 540 medical record files, there were 131 incomplete medical record files which were used as the population and used a sample of 99 medical record files. The research was conducted on January 9-February 17, 2023. The results showed that of the 99 medical record files on the patient's medical resume items, the majority 75 (75.8%) were complete, the minority 24 (24.2%) were incomplete, assessment initial medical majority 88 (88.9%) complete files, minority 11 (11.1%) incomplete, majority nursing assessment complete 99 (100%), cppt majority 83 (83.8%) complete files, minority 16 (16.2%) were incomplete, the majority of hand over forms were 99 (100%) complete, the majority of medical cards were 87 (87.9%) complete, the minority were 12 (12.1%) incomplete and the majority of nutritional care forms are complete 99 (100%). Based on the results of the study, it can be concluded that the incomplete inpatient medical record files at RSUD Dr. Pirngadi Medan City were affected by PPA's lack of compliance and discipline in filling out medical record files. It is expected that all PPAs can write down all examination actions in the patient's medical record file completely.